PERAN PG-PAUD UHAMKA DALAM PENDAMPINGAN KOMUNITAS MATAHARI KECIL DALAM MENINGKATKAN KUALITAS PENDIDIKAN ANAK USIA DINI - Mil, Silvie; Ekawati, Anita Dewi (Jurnal Abdimas, 2018)
To serve a good education is not only become government responsibility, but also higher education institutions that produce human resources such us teachers and it also become society’s responsibilities. In order the quality of early childhood education, a partnership is needed which in this case involves the University of Muhammadiyah Prof. Dr. Hamka, Matahari Kecil as a non-governmental organization and private kindergarten Warga Teladan. This was realized through the holding of the Community Partnership Program "Training on Volunteer Communities in the Small Sun Community as a companion teacher in the TK Warga Teladan, Jakarta". This activity is intended to provide knowledge strengthening for Warga Teladan kindergarten teachers and volunteers from the Matahari Kecil Community in terms of Early Childhood Education. In this workshop, the participants also trained their skills in preparing lesson plans at TK Warga Teladan. This is important because almost all of the volunteers who manage the TK Warga Teladan came from non-educational backgrounds and still do not fully understand about early childhood education and teachers are also not optimal in developing lesson plans in order to improve the quality of education in TK Warga Teladan. As the result, the workshop is aim that all of participants knowledge in early childhood education will increase and so does their skill in construct the lesson plans.